Intolerance Uncertainty as a Moderator between Religiosity and Psychological Well-Being in Unemployment - Muslim, Abdul Aziz; Rafica, Vivia Maya (LPPM Undiksha, 2021)
A positive attitude in an individual can be formed if he has good psychological well-being. A good form of psychological well-being can organize oneself according to predetermined goals. The unemployed have very low psychological well-being so that many psychological problems. Many studies have linked religiosity with psychological well-being, with the result that there is a positive correlation between religiosity and psychological well-being. This study aims to analyze the influence of religiosity and psychological well-being defined by intolerance of uncertainty. This research subjects were 220 persons unemployed; they were 74 men and 146 women. The data of this research was collected by using some instruments, such as Orientation Scale-Revised (ROS-R), Intolerance of Uncertainty Scale (IUS-12), and Psychology Well Being Scale (PWBS). The data analysis of this research used Moderated Regression Analysis (MRA). The result of this research indicated that there was correlation between religiosity and psychological well-being (β = 0,707, p = 0,000), despite the correlation is getting weak when it is mediated by intolerance of uncertainty (β = -0,045, p = 0,046). This study proves that religiosity can directly affect the psychological well-being of individuals. This is evidenced by high religiosity, which has a positive and significant correlation to high psychological well-being. However, moderated by high yield uncertainty intolerance can weaken the relationship between religiosity on the psychological well-being of individuals.